Pengaruh Beban Kerja dan Komunikasi Terhadap Kepuasan Kerja Melalui Mediasi Stres Kerja Dan Hubungan Rekan Kerja (Studi Pada Karyawan Bank BJB KCU Rangkasbitung) - Nugraha, Fajriana; Suherna, Suherna (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2019)
Job satisfaction in general leads to the attitude of employees on the job. There are various things that allegedly can affect the high low job satisfaction in this study taken workload, communication, work stres and peer relations. This study aims to determine whether the workload and communication affect the job satisfaction is mediated by work stres and peer relationships. The study used SEM-PLS analysis with sampling of 100 employees at BJB Rangkasbitung office. Based on the results of hypothesis testing showed that: 1) Work load has a negative and significant effect on job satisfaction; 2) Communication has a positive and significant impact on job satisfaction; 3) Work load positively affects work stres; 4) Communication has a positive and significant effect on the relationship of colleagues; 5) Positive and significant work stres affect the job satisfaction; and 6) Relationship of colleagues have positive and significant impact on job satisfaction.